WHO’S AFRAID OF A NON-ADAPTABLE CONSTITUTION? - Terence Rajivan Edward (IJRDO - Journal of Social Science and Humanities Research, 2023)
Joseph Raz criticizes John Rawls for a procedure supporting a non-adaptable constitution. This paper considers how a non-adaptable constitution can seem not so counterintuitive and also when.